A novel thermal–hydraulic–mechanical model for the enhanced geothermal system heat extraction. (September 2016) - Cao, Wenjiong; Huang, Wenbo; Jiang, Fangming
Highlights: A 3D model describing THM multi-physical coupling is developed for EGS. The model is of three salient features. Results unravel the well-defined coupling mechanisms for the EGS heat extraction. Major parameters affecting the THM effects are analyzed in detail. Abstract: The present work reports on the development of a three-dimensional transient model, which describes the multi-physical coupling of thermal (T), hydraulic (H), and mechanical (M) processes during heat extraction of enhanced geothermal systems (EGS). The model encompasses: (1) local thermal non-equilibrium to formulate the convective heat exchange between rock matrix and heat transfer fluid in the reservoir, (2) sub-modules describing temperature- and pressure-dependent thermophysical properties of water, and (3) a thermo-poroelastic model, which is used to calculate the effective stress in the rock matrix and to determine the time-changing local porosity and permeability in the reservoir. Analyses for an idealized EGS indicate that an increased effective stress in the rock matrix yields significant mechanical effects upon the EGS heat extraction performance, namely: for a given injection pressure the mass flow rate of fluid is enhanced, leading to improved heat extraction, while the life expectancy of the EGS is shortened. It is found from additional simulations that: (1) a decrease in injection temperature and an increase in injection pressure can lead to an increase at the magnitude of the negative effective stress, which, in turn, can enlarge the porosity and permeability in the heat reservoir, and (2) a smaller value of ha reduces the heat exchange between the rock and the fluid as it reduces the magnitude of the effective stress.